Pelatihan Teknik Fotografi EDFAT Mahasiswa UIN K.H. Abdurrahman Wahid Pekalongan untuk Meningkatkan Pesan Visual Moderasi Beragama - Dimas Prasetya; Arditya Prayogi; Ryan Marina; Afina Fahru Miliana (Lembaga Pengembangan Kinerja Dosen, 2024)
In the digital era, journalistic photography has a strategic role in conveying effective messages through visual elements. Visually, the use of journalistic photography is not only used as a complement to text news, but helps readers understand the messages in an event more clearly and in depth. Among the messages that can be conveyed through journalistic photography is the visual message of religious moderation, which includes the value of tolerance, openness, and harmony between religious believers. Using the Participatory Action Research (PAR) method, this research aims to implement EDFAT (Entire, Detail, Frame, Angle, Time) photography technique training for the students of UIN K.H. Abdurrahman Wahid Pekalongan who have an interest and focus on the field of Islamic journalism. Through this training, students are equipped with technical photography skills to produce journalistic photography works that can support the amplification of religious moderation messages in digital media. This research concludes that the EDFAT technique is a relevant method for producing photographic works that are not only visually attractive but also effective in amplifying messages of religious moderation.